The Bernese peri-acetabular osteotomy through a modified approach. A technical note. (March 2013) - Whittingham-Jones, Paul; Kirit Patel, Nirav; Hashemi-Nejad, Aresh
Abstract: Introduction: A modification of the technique for performing the Bernese periacetabular osteotomy is described. Materials and methods: A medial approach to the Ischium and a subtle re-orientation of the pubic osteotomy are detailed. Conclusion: Surgical morbidity is likely decreased with a concurrent cosmetic advantage without compromise to surgical correction or patient safety.